ABC-model analysis of gain-switched pulse characteristics in low-dimensional semiconductor lasers. (January 2018) - Bao, Xumin; Liu, Yuejun; Weng, Guoen; Hu, Xiaobo; Chen, Shaoqiang
Abstract: The gain-switching dynamics of low-dimensional semiconductor lasers is simulated numerically by using a two-dimensional rate-equation model. Use is also made of the ABC model, where the carrier recombination rate is described by a function of carrier densities including Shockley – Read – Hall (SRH) recombination coefficient A, spontaneous emission coefficient B and Auger recombination coefficient C . Effects of the ABC parameters on the ultrafast gain-switched pulse characteristics with high-density pulse excitation are analysed. It is found that while the parameter A has almost no obvious effects, the parameters B and C have distinctly different effects: B influences significantly the delay time of the gain-switched pulse, while C affects mainly the pulse intensity.